1996
DOI: 10.1002/(sici)1097-4628(19960103)59:1<99::aid-app15>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of polyester yarns modified by trichloroacetic acid-methylene chloride treatment

Abstract: SYNOPSISThe effect of trichloroacetic acid-methylene chloride (TCAMC) solvent system on the mechanical properties of poly(ethy1ene terephtha1ate)-based flat, high twist, and spun yarns were studied. Pretreatments were carried out in an unrestrained state at different concentrations for various times and without employing any heat treatment. The stress-strain behavior of yarns was analyzed. The stress-strain curves showed that the treated yarns exhibit different morphologies. A significant plastic flow region c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Besides highly elastic material and crystalline solids, there are certain polymers which can undergo large‐scale deformation without significant fracture up to certain level, but do not completely return to their original length upon the removal of stress. However, they show elastic behavior at smaller strains at the Hookean region 25. This behavior is observed in the stress–strain curves of the FFP and MDP yarns treated with the TCAC reagent.…”
Section: Resultsmentioning
confidence: 86%
“…Besides highly elastic material and crystalline solids, there are certain polymers which can undergo large‐scale deformation without significant fracture up to certain level, but do not completely return to their original length upon the removal of stress. However, they show elastic behavior at smaller strains at the Hookean region 25. This behavior is observed in the stress–strain curves of the FFP and MDP yarns treated with the TCAC reagent.…”
Section: Resultsmentioning
confidence: 86%
“…According to the solubility parameter theory it has been established [33,34] that highly interacting solvents, after diffusion into the polymer structure, promote crystallisation, re-crystallisation of the molecules and increase their segmental mobility so that structural modifications take place. It will be mentioned that PET Table 2 that there is no appreciable increase in X-ray crystallinity at lower concentration of 1% and 3% TCAMC treatment.…”
Section: Effect Of Tcamc On Crystallinity Of Pet Fabricmentioning
confidence: 99%
“…4). Previous research has also shown that such treatments increase the cohesion between fibres [17,18].…”
Section: Effect On Abrasive Wear Resistancementioning
confidence: 99%
“…One approach that has been explored to a considerable extent is the structural modification of regular polymeric fibres making use of highly interacting solvents. It has been demonstrated that the interacting power of Trichloroacetic acid-methylene chloride (TCAMC) solvent system with Polyethylene terephthalate (PET) is very high and the regent attacks the polymer matrix, disintegrates and finally dissolves out the PET at about 25% (w/v) concentration in 5 minutes at room temperature condition [17][18][19][20][21]. It is expected that at certain lower concentration of TCAMC treatment, the compact structure of PET opens up and as a result, molecular rearrangements may take place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation